‘The gentlest of predations’: Photography and privacy law - C. Ludlow (Law Text Culture, 2006)
In December 2004, Peter James Mackenzie, a labourer from the beachside suburb of Coogee in Sydney, pleaded guilty before a magistrate to a charge of offensive behaviour for photographing women who were bathing topless at the beach without their knowledge or consent. He forfeited his expensive Nokia mobile camera phone and the images he had taken. ‘[The women] were quite horrified by what you were doing … Women are not objects of decoration for men’s gratification,’ said Magistrate Lee Gilmour as she fined him 500 (The Sydney Morning Herald 2 December 2004).